2007
DOI: 10.1590/s0103-50532007000700002
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of digitoxigenin by Cochliobolus lunatus

Abstract: A reação de biotransformação da digitoxigenina (1) por Cochliobolus lunatus foi investigada. Foram realizados experimentos com duração de 4 dias, que resultaram no isolamento de quatro produtos, cujas estruturas químicas foram elucidadas como sendo 1β-hidroxidigitoxigenina (2), 7β-hidroxidigitoxigenina (3), 8β-hidroxidigitoxigenina (4) e digitoxigenona (5). A obtenção desses produtos nas condições empregadas nunca foi anteriormente descrita. A produção da substância 4 em uma reação de biotransformação também é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It is important to fully comprehend the economic benefits of the cryptic Cochliobolus complex at the organismal level, such as their role in the production of industrial enzymes [ 195 ], medications [ 196 ], and bioremediation [ 194 ], biodiesel [ 197 ]. Bioremediation is the capacity of microorganisms to break down (detoxify) harmful chemicals and undesirable organic compounds into non-toxic molecules [ 198 ].…”
Section: In Bioremediation and Waste Biomass Valorizationmentioning
confidence: 99%
“…It is important to fully comprehend the economic benefits of the cryptic Cochliobolus complex at the organismal level, such as their role in the production of industrial enzymes [ 195 ], medications [ 196 ], and bioremediation [ 194 ], biodiesel [ 197 ]. Bioremediation is the capacity of microorganisms to break down (detoxify) harmful chemicals and undesirable organic compounds into non-toxic molecules [ 198 ].…”
Section: In Bioremediation and Waste Biomass Valorizationmentioning
confidence: 99%
“…Curvularia lunata has been used as a tool to understand the effects of pH and glucose concentration on the production of rifamycin oxidase in a batch reactor (Banerjee and Srivastava, 1993 ). Pádua et al ( 2007 ) reported that Cochliobolus lunatus mediated biotransformation of digitoxigenin produces 1β-hydroxydigitoxigenin, 7β-hydroxydigitoxigenin, 8β-hydroxydigitoxigenin, and digitoxigenone as transformation products. Rifamycin B which is a clinically less active anti-biotic is transformed into Rifamycin S which is more potent and active by using rifamycine oxidase derived from Curvularia lunata which has a great commercial significance (Jobanputra et al, 2003 ).…”
Section: As a Tool In Biotransformationmentioning
confidence: 99%
“…For the hydroxylation of steroids, biotransformation has been widely accepted as an available way due to the comparatively higher stereo-selectivity [12,13], and some microbial hydroxylation methods, such as 11α-and 11β-hydorxylation, have already been industrially applied for decades [14,15]. Up to now, some lamentous fungi that can hydroxylate steroids at C7β have been screened to allow the production of 7β-OHSt by microbial transformations [16][17][18].…”
Section: Introductionmentioning
confidence: 99%